Cellular and Molecular Mechanisms of Anti-Phospholipid Syndrome - Radic, Marko; Pattanaik, Debendra (Frontiers in Immunology, 2018)
The primary anti-phospholipid syndrome (APS) is characterized by the production of antibodies that bind the phospholipid-binding protein β2 glycoprotein I (β2GPI) or directly recognize negatively charged membrane phospholipids in a manner that may contribute to arterial or venous thrombosis. Clinically, the binding of antibodies to β2GPI could contribute to pathogenesis by formation of immune complexes or modification of coagulation steps that operate along cell surfaces. However, additional events are likely to play a role in pathogenesis, including platelet and endothelial cell activation. Recent studies focus on neutrophil release of chromatin in the form of neutrophil extracellular traps (NETs) as an important disease contributor. Jointly, the participation of both the innate and adaptive arms of the immune system in aspects of the APS make the complete understanding of crucial steps in pathogenesis extremely difficult. Only coordinated and comprehensive analyses, carried out in different clinical and research settings, are likely to advance the understanding of this complex disease condition.